A Challenge of Economic Statecraft - Zoellick, Robert B. (World Bank, Washington, DC, 2018)
The World Bank Group has sketched six strategic themes to alert us to necessities and opportunities as Fate hurries past. They focus our attention on new development solutions for the poorest countries; states facing breakdown or coming out of conflict; middle income countries, integrating public goods, such as climate change, into our work; opportunity in the Arab world; and continually upgrading our knowledge and learning.The challenge is to take practical steps, now, that require work and will, guided by a strategic outlook. What is more fundamental than seizing the opportunity of a changing global landscape? This is the challenge of economic statecraft.